Tapping Mode Atomic Force Microscopy (TMAFM) of Some Multi-Component Polymers - Adhikari, Rameshwar (Journal of Nepal Chemical Society, 2013)
Atomic force microscopy (AFM) has been used frequently in polymer research in particular for imaging topography and phase morphology of multi-component polymers. In this work, we demonstrate the potential applications of the AFM in the study of morphology of multi-component polymers taking examples of some technically important semicrystalline polymers, blends and nanostructured block copolymers. The morphology of semicrystalline morphology could be determined ranging from molecular arrangement in the unit cells to the lamellar structure to the macroscopic morphology showing the spherulites of the polymers. Nanoscale morphology of block copolymers, nanocomposites and blends could be easily accessed by the aping mode AFM (TMAFM) phase imaging technique. It has been demonstrated that TMAFM phase imaging can be successfully utilized as a routine tool for the investigation of nanoscale morphology of the heterogeneous polymers. DOI: http://dx.doi.org/10.3126/jncs.v29i0.9258 Journal of Nepal Chemical Society Vol. 29, 2012 Page: 96-103 Uploaded date: 12/5/2013